Integrative taxonomy reveals three new species and one new record of Psychropotes (Holothuroidea, Elasipodida, Psychropotidae) from the Kermadec Trench region and the Wallaby-Zenith Fracture Zone - Xiao, Yunlu; Zhang, Haibin (PeerJ, 2025)
The holothuroid genus Psychropotes is the largest genus in the family Psychropotidae. Prior to this study, this genus contained 20 accepted species and was prominent representatives in the deep-sea benthic fauna at lower bathyal-abyssal depths throughout the global oceans, but it has been poorly studied in the hadal zone. Deep-sea holothuroids were collected in October 2022 to March 2023 by the joint China-New Zealand deep-diving scientific expedition to the Kermadec Trench in the South Pacific Ocean and the Wallaby-Zenith Fracture Zone in the East Indian Ocean at a depth of 6,018–6,605 m. Our examination of specimens of Psychropotes revealed three new species, which we described as Psychropotes diutiuscauda sp. nov., Psychropotes nigrimargaria sp. nov., and Psychropotes asperatus sp. nov. We also recorded Psychropotes depressa (Théel, 1882) for the first time from the Kermadec Arc at a depth of 1,620 m. We provide comprehensive descriptions of the morphological features and a taxonomic key for the genus Psychropotes. We also performed a phylogenetic analysis of the order Elasipodida based on COI sequences and the concatenated 16S-COI sequences. Intraspecific and interspecific genetic distances were calculated among Psychropotes Species based on COI sequences. Our phylogenetic analyses supported the assignment of three new species to the genus Psychropotes and their differentiation from congeners. The geographical distribution and global depth range of psychropotid species were summarized, and the results showed that the Pacific region had the highest species diversity. These findings contribute to the taxonomic diversity and patterns of geographical distribution in the family Psychropotidae.
Keywords: Deep-sea; Hadal zone; Morphology; New species; Phylogeny; Systematics